POTENTIAL IMPACT OF THE 2017 ACC/AHA HIGH BLOOD PRESSURE GUIDELINE IN NORMOTENSIVE PATIENTS WITH STABLE CORONARY ARTERY DISEASE: INSIGHTS FROM THE CLARIFY REGISTRY. (June 2018) - Vidal-Petiot, E.; Sorbets, E.; Bhatt, D.; Ducrocq, G.; Elbez, Y.; Ferrari, R.; Ford, I.; Tardif, J.-C.; Tendera, M.; Fox, K.; Steg, P.G.
Abstract: Objective: The 2017ACC/AHA high blood pressure (BP) guideline lowered the threshold defining hypertension and BP target in high-risk patients to 130/80 mmHg, Patients with coronary artery disease (CAD) and systolic BP 130–139 mmHg or diastolic BP 80–89 mmHg should now receive medication to achieve this target. We aimed to investigate the relationship between BP and cardiovascular events in "real-life" CAD patients considered as normotensive until the recent guideline. Design and method: Data from patients with stable CAD, with no history of hypertension and baseline BP < 140/90 mmHg, receiving > = 1 BP-lowering medication prescribed for angina, enrolled in the international CLARIFY registry from November 2009 to June 2010, were analyzed. Patients with heart failure were excluded. A Cox proportional hazards model was used to evaluate the relationship between average BP during follow-up and cardiovascular outcomes. SBP subgroups were defined as < 120 mmHg, 120–129 mmHg (reference), 130–139 mmHg, and > = 140 mmHg. DBP subgroups were defined as < 60, 60–69 mmHg, 70–79 mmHg (reference), 80–89 mmHg, and > = 90 mmHg. The primary endpoint was the composite of cardiovascular death, myocardial infarction and stroke, and secondary endpoints were each component of the primary endpoint. Results: In 5826 patients (median follow-up 5.0 years), diastolic BP 80–89 mmHg, but not systolic BP 130–139 mmHg, was associated with an increased risk of the primary endpoint (adjusted HRs 1.81, 95% CI 1.09–2.99, and 0.80, 95%CI 0.46–1.40, versus 70–79 mmHg and 120–129 mmHg, respectively). Similar results were observed for cardiovascular death and stroke. No significantly increased risk was observed for systolic BP < 120 mmHg for either endpoint (HR 1.26, 95% CI 0.76 - 2.07, for the primary endpoint). Diastolic BP < 70 mmHg was associated with an increased risk of the primary outcome, but the same was observed for stroke, suggesting a degree of reverse causality. Conclusions: In this population of stable CAD patients defined as normotensive according to the 140/90 mmHg threshold, and receiving antianginal BP-lowering medication, achieved diastolic BP 80–89 mmHg was associated with increased cardiovascular risk while achieved systolic BP 130–139 mmHg was not, supporting the lower diastolic but the not the lower systolic BP hypertension-defining threshold and treatment target.